The transition to headship - Berry, Jill (2016)
Transition into first-time headship is a challenge, as the new leader lets go of their former role as a teacher/deputy and at the same time prepares to adopt a new professional persona. This research explores the nature of transition as experienced by six deputies moving to be heads of independent schools which are new to them. It identifies what is distinctive about the experience and what can be learnt which may be of benefit to future generations of new headteachers and the schools they join. It focusses on the challenges inherent in making this transition, and the strategies these fledgling heads adopt as they navigate the process. Six research participants are tracked through the final months of their deputy headship and into the early months of their first headship. They simultaneously let go of their deputy role, paving the way for their successors in that role, while preparing to take on the professional responsibilities of the headteacher. Socialisation into this new role is reciprocal, as the new head affects, and is affected by, the school community they join. The new heads negotiate the tension, and attempt to find balance, between inheriting the role from their predecessor and inhabiting this role and making it their own. The time in between being appointed to headship and formally assuming the position offers these heads-elect the opportunity to begin to divest themselves of their deputy role and take on the mantle of the school leader. During this lead-in period these incoming heads devise strategies, access support, explore and experiment as they continue the process of formulating and articulating their conception of the head they hope to be, and begin their tentative steps towards realising that vision. In addition to data from semi-structured interviews, shadowing these deputies/new heads and discussion with those who worked most closely with them, and who knew them best, opened up a wider perspective on the two-way socialisation process and the nature of transition to headship.